Desenvolvimento profissional do médico professor: um estudo de caso na Universidade Federal de Uberlândia - Silva, Wellington dos Reis (2014)
The aim of this study was to understand the professional development of the medical professor at the Federal University of Uberlândia, based upon their professional experiences in teaching. The questions that guided the research were: How does the professional development process occur for medical professors? What are the main complaints, challenges and strategies used by professors in the medical field when teaching in tertiary education? What are the main factors that contribute to the formation of the teaching identity process? What is the knowledge of the medical professors, how have they built it up and how do they deploy it? How does the teaching learning process occur? This is a Case Study with a qualitative approach. To guide analysis, we have used the scientific production in the area such as Marcelo (2009), Tardif (2002), Melo (2007), Cunha (2004, 2007), Pimenta (2005, 2002), as well as documents that depict the history of the institution, laws and guidelines related to higher education and medical courses. Data was collected through two questionnaires, a simplified and an in-depth one. The analysis indicated that the professional development of the medical professors of UFU occurs throughout their teaching career, which involves specific demands from the area, mentoring and aspects related to the following dimensions: personal and professional. The teaching practice of the medical professors is predominantly underpinned by experiential knowledge. The main complaints and challenges faced by medical professors are related to working conditions, such as the overload of activities, which makes it difficult to balance between teaching, research and University extension, lack of incentives for participation in continuing educational courses for professors in the medical field and not to mention low salaries due to the devaluation of the teaching career. Among the strategies identified by the medical professors to overcome these difficulties are: the search for continuing education in medical teaching, stimulating postgraduate degrees, research and policies for teaching appreciation, as well as institutional support. Regarding the identity process of the medical professor, there is a direct link to his/her life story, which involves both the personal and professional dimensions in a way that the phases of life and profession intertwine at a variety of moments. In this sense, the study points toward the need for institutional training policies, appreciation and professional enhancement of the medical professors, which is certainly reflected in the constant improvement of the educational process developed in the undergraduate courses.